c-Jun Amino Terminal Kinase Signaling Promotes Aristolochic Acid-Induced Acute Kidney Injury - Fan Yang (Frontiers in Physiology, 2021)
Aristolochic acid (AA) is a toxin that induces DNA damage in tubular epithelial cells of the kidney and is the cause of Balkan Nephropathy and Chinese Herb Nephropathy. In cultured tubular epithelial cells, AA induces a pro-fibrotic response via the c-Jun amino terminal kinase (JNK) signaling pathway. This study investigated the in vivo role of JNK signaling with a JNK inhibitor (CC-930) in mouse models of acute high dose AA-induced kidney injury (day 3) and renal fibrosis induced by chronic low dose AA exposure (day 22). CC-930 treatment inhibited JNK signaling and protected from acute AA-induced renal function impairment and severe tubular cell damage on day 3, with reduced macrophage infiltration and expression of pro-inflammatory molecules. In the chronic model, CC-930 treatment inhibited JNK signaling but did not affect AA-induced renal function impairment, tubular cell damage including the DNA damage response and induction of senescence, or renal fibrosis; despite a reduction in the macrophage pro-inflammatory response. In conclusion, JNK signaling contributes to acute high dose AA-induced tubular cell damage, presumably via an oxidative stress-dependent mechanism, but is not involved in tubular atrophy and senescence that promote chronic kidney disease caused by ongoing DNA damage in chronic low dose AA exposure.